Efeitos da suplementação de whey proteins, inoculação de decanoato de nandrolona e treinamento resistido por 12 semanas sobre perfil lipidico e tecido adiposo visceral de ratos wistar - MACAU, Diego Antonio de Jesus (2021)
Introduction: Currently, one of the biggest concerns worldwide is the high prevalence of individuals with due to the accumulation of body fat. This fact is associated with a series of comorbidities generating a high risk to the individual's health. Objective: To verify the effects of whey proteins 2g/kg/day, resistance training for 12 weeks and nandrolone decanoate inoculation on the visceral adipose tissue and lipid profile of Wistar rats. Materials and Methods: sample of 20 rats of the Wistar lineage divided into 4 groups containing 5 animals each, as follows: control (C) standard food and water, whey proteins group and 1mg/kg/week nandrolone decanoate supplemented with 2g/ kg/day of whey proteins (WD), resistance training group and inoculation of 1mg/kg/week of nandrolone decanoate (TD) and resistance training group, supplementation of 2g/kg/day of whey proteins and inoculation of 1mg/kg/ week of nandrolone decanoate (TWD). The rats remained on a 12-hour light-dark lighting cycle fed chow and water ad Libidum. After euthanasia, the analysis of serum parameters and weighing of the retroperitoneal and mesenteric fat compartments and the gastrocnemius muscle were performed. Results: There was a gain in body mass in all groups at the end of the experiment, however only group C showed a high Lee index. Group C had higher mean body mass, mesenteric fat, retroperitoneal fat and cholesterol when compared to the trained groups. There was no difference between the WD, TD and TWD groups. Discussion: The parameters analyzed in this study showed greater body mass in the control group rats. Studies that investigated training and supplementation with 2, 4 and 6 g/kg of whey proteins showed greater body mass when compared to the supplemented groups in this study. The groups that received nandrolone decanoate were within the normal range for weight, visceral fat and increased muscle mass, which is in agreement with the findings in the literature. Conclusion: Nandrolone decanoate, associated with resistance training and whey proteins supplementation caused a significant reduction in visceral adipose tissue and total cholesterol in Wistar rats.